Forest Water Governance - Challenges in Cross-Sectoral and Multi-Level Collaboration - Mancheva, Irina (Socialmedicinsk tidskrift, 2020)
The aim of this thesis is to explore and explain the challenges related to the governance of a resource that requires cross-sectoral multi-level governance and to examine the role of the state in those interactions. The thesis includes a mix of quantitative (survey and aerial photographs) and qualitative (interviews, analysis of documents and meeting observations) research methods for investigating forest water governance across national, regional and local levels. Empirically, it involves four case studies analysing units embedded in the larger case – namely cross-sectoral governance of forest water.